2011
DOI: 10.1111/j.1365-2095.2009.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

α-Tocopherol in weaning diets for European sea bass (Dicentrarchus labrax) improves survival and reduces tissue damage caused by excess dietary DHA contents

Abstract: The objective of the present study was to investigate the combined effect of several dietary contents of vitamin E and polyunsaturated fatty acids (PUFA), mainly docosahexaenoic acid (DHA), on growth, survival, biochemical composition and tissue morphology of sea bass along early development. A feeding experiment was conducted in sea bass larvae using five different diets with the same proximate composition and different ratios of DHA concentrated fish oil [10, 30 and 50 g kg−1 dry weight (DW)] and vitamin E (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 61 publications
(112 reference statements)
6
65
0
1
Order By: Relevance
“…Although lipid intake and lipid gain increased with the increase in dietary lipids, the low LRE, an indicator of poor lipid retention, showed by fish fed with D15 follows the same trend of teleost pejerrey Odontesthes bonariensis, when fed lipid levels higher than 25 % (Gómez-Requeni et al 2013). Betancor et al (2011) reported that HUFA (mainly DHA) was readily deposited in fish tissues and associated with higher sea bass mortalities because of increased peroxidation risks, and dietary DHA contents up to 5 % severely increased the incidence of muscular lesions and the presence of ceroid pigment within hepatocytes. Therefore, the reduced fatty acid absorption efficiency and ultimately juvenile growth might be because of high dietary levels of HUFA levels (such as 20:5n-3, 22:5n-3 and 22:6n-3) which are highly susceptible to being oxidized and triggering in vivo oxidative stress in the test fish.…”
Section: Discussionmentioning
confidence: 57%
“…Although lipid intake and lipid gain increased with the increase in dietary lipids, the low LRE, an indicator of poor lipid retention, showed by fish fed with D15 follows the same trend of teleost pejerrey Odontesthes bonariensis, when fed lipid levels higher than 25 % (Gómez-Requeni et al 2013). Betancor et al (2011) reported that HUFA (mainly DHA) was readily deposited in fish tissues and associated with higher sea bass mortalities because of increased peroxidation risks, and dietary DHA contents up to 5 % severely increased the incidence of muscular lesions and the presence of ceroid pigment within hepatocytes. Therefore, the reduced fatty acid absorption efficiency and ultimately juvenile growth might be because of high dietary levels of HUFA levels (such as 20:5n-3, 22:5n-3 and 22:6n-3) which are highly susceptible to being oxidized and triggering in vivo oxidative stress in the test fish.…”
Section: Discussionmentioning
confidence: 57%
“…(2008) used 1.5 and 3.0 g kg −1 dry diet of α‐TOH for gilthead seabream and sea bass, and suggested an optimal level of 3 g kg −1 because this high level reduced mortality after stress, but not the mortality under standard rearing conditions. In the same study, the high α‐TOH level also alleviated muscular lesions caused by excessive dietary DHA (Betancor et al. 2011).…”
Section: Larval Nutritionmentioning
confidence: 86%
“…Moreover, the increase in dietary levels of vitamin E reduced the incidence of these muscular lesions (Betancor et al . ). However, this beneficial effect of vitamin E was not observed in this study when 5% of DHA was included in the diet, suggesting that the addition of vitamin E alone as an antioxidant is not enough to control lipid peroxidation when high levels of DHA are included in fish larvae diets.…”
Section: Discussionmentioning
confidence: 97%
“…In a previous study, an increase in the incidence of muscle lesions was observed in sea bass larvae, Dicentrarchus labrax (L.), fed increasing levels of DHA, particularly when vitamin E levels were low (Betancor et al . ) Several reasons may explain the higher susceptibility of muscular tissues to free radical injury. For instance, muscle is prone to oxidative injury as a result of increased electron flux because of its requirement and ability to undertake rapid and coordinated changes in energy supply and oxygen flux during contraction (Haycock et al .…”
Section: Introductionmentioning
confidence: 99%